2008
DOI: 10.1016/j.canlet.2008.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3β induces apoptosis in cancer cells through increase of survivin nuclear localization

Abstract: Glycogen synthase kinase 3β (GSK3β) regulates numerous signaling pathways that control a wide range of cellular processes, including cell proliferation, differentiation, apoptosis and metabolism. We report a novel function of GSK3β: It interacts with the inhibitor-of-apoptosis protein (IAP) survivin to modulate its expression, thus regulating apoptosis in human lung cancer cells. A coimmunoprecipitation assay revealed that GSK3β can bind survivin. Activation of GSK3β induced translocation of survivin from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 35 publications
(41 reference statements)
1
34
0
2
Order By: Relevance
“…As a core component of certain pathways involved in a number of cancers, such as the Wnt and Hedgehog pathways, GSK-3β plays a role in multiple cell processes including cell growth, differentiation, cell survival, and proliferation (24)(25)(26). Decreased GSK-3β expression may promote mammary tumorigenesis and increase the number of cells in the S phase (27,28). Our results showed that the increased phosphorylation of GSK-3β at Ser9 in U-87MG/ SPARC shRNA, which in turn inactivates GSK-3β enzymatic activity (29), may be another signal molecule associated with growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…As a core component of certain pathways involved in a number of cancers, such as the Wnt and Hedgehog pathways, GSK-3β plays a role in multiple cell processes including cell growth, differentiation, cell survival, and proliferation (24)(25)(26). Decreased GSK-3β expression may promote mammary tumorigenesis and increase the number of cells in the S phase (27,28). Our results showed that the increased phosphorylation of GSK-3β at Ser9 in U-87MG/ SPARC shRNA, which in turn inactivates GSK-3β enzymatic activity (29), may be another signal molecule associated with growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat surprising given that borealin interacts with survivin at its homodimerisation interface and could potentially mask part of the central NES ( Figure 2B), nevertheless, it points to the subtleties lying within the structure of this tiny protein. As mentioned above redistribution of survivin into the nucleus is promoted by activation of GSK3B, and although it is not yet known whether survivin is a substrate of this kinase, GSK3B can bind survivin directly and has a bipartite NLS (Li et al, 2008).…”
Section: Getting Into the Nucleusmentioning
confidence: 97%
“…Survivin acetylation, which occurs at K129, and is facilitated by the acetyl transferase CREB-binding protein (CBP), has been implicated in aiding survivin transit out of the nucleus (Wang et al, 2010), presumably by affecting the activity of the C-terminal NES (Engelsma et al, 2007). Glucogen synthase kinase 3β (GSK3β) facilitates translocation of survivin into the nucleus, but whether phosphorylation of survivin by GSK3β is involved is not yet known (Li et al, 2008). Work from my lab has recently provided two lines of evidence that suggest that casein kinase 2 (CK2) phosphorylation helps to maintain survivin within the cytoplasm, as treatment with the CK2 specific inhibitor, TBB (4,5,6,7-tetrabromobenzotriazole), or mutation of threonine 48 (T48), the unique site targeted by CK2 in survivin, causes its accumulation in the nucleus (Barrett et al, 2011).…”
Section: Active Export Keeps Survivin Out Of the Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…After being washed with PBS, the cells were incubated with a fluorescein isothiocyanate-tagged anti-biotin monoclonal antibody (1:500) at 37°C for 1 h and then observed by fluorescent microscopy. 18 Peroxidase was transformed with substrate at 37°C for 30 min; finally, slices were stained with DAB and counterstained lightly with hematoxylin. The samples without the addition of enzyme were regarded as positive controls.…”
Section: Measurement Of Myocardial Apoptosis (In Situ End-labeling Tumentioning
confidence: 99%